2001
DOI: 10.1095/biolreprod65.6.1672
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Renin-Angiotensin System in the Bovine Ovary: Cyclic Variation of the Angiotensin II Receptor Expression1

Abstract: Angiotensin (Ang) II may modulate reproductive function in the bovine ovary. Therefore, expression and localization of a local ovarian renin-angiotensin system (RAS) were investigated by elucidating the influence of the estrus cycle, pregnancy, and the presence of follicular cysts. Receptor analysis and autoradiography were used to characterize and localize Ang II receptors. Cyclic variations in the density of ovarian Ang II receptors were found with a higher value in estrus than in diestrus. The density in ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…In monovular species, the expression of AGTR2 receptor was first identified in theca cells from bovine dominant follicles (Schauser et al 2001). These data were further confirmed by Berisha et al (2002) who demonstrated mRNA-encoding AGTR1 and AGTR2 receptors in both theca and granulosa cells from bovine and observed a slight increase in AGTR2 mRNA in theca cells from highly estrogenic follicles (O180 ng/ml) in comparison with less estrogenic follicles (20-180 ng/ml).…”
Section: Ang II Receptors In Follicular Cellsmentioning
confidence: 56%
See 1 more Smart Citation
“…In monovular species, the expression of AGTR2 receptor was first identified in theca cells from bovine dominant follicles (Schauser et al 2001). These data were further confirmed by Berisha et al (2002) who demonstrated mRNA-encoding AGTR1 and AGTR2 receptors in both theca and granulosa cells from bovine and observed a slight increase in AGTR2 mRNA in theca cells from highly estrogenic follicles (O180 ng/ml) in comparison with less estrogenic follicles (20-180 ng/ml).…”
Section: Ang II Receptors In Follicular Cellsmentioning
confidence: 56%
“…Schauser et al (2001) observed intense AGTR2 receptor binding in cow periovulatory follicles, mainly in the theca cells. Using an in vivo model, our group demonstrated that i.m.…”
Section: Ang II Signaling and Receptors Near Ovulationmentioning
confidence: 82%
“…The present study identified a discrete RAS within the ovarian stroma and its blood vessels, including renin gene expression, angiotensinogen and ANG II protein and ACE binding. Of particular importance when attributing a function to the stromal RAS, is the localisation of AT 1a receptor mRNA to the stroma adjacent to large follicles and corpora lutea, a finding previously reported in the bovine ovary (Schauser et al 2001). The AT 1a receptor is viewed to elicit most of the cell growth and angiogenic properties of ANG II (Chung et al 1998), and it is therefore likely that ANG II at this site influences processes such as blood flow, vascularisation and growth of developing follicles via this receptor.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies in the rat have also reported angiotensin receptors to be absent in corpora lutea (Obermuller et al 1998), while other studies have reported angiotensin receptors in cultured luteal cells (Pepperell et al 1993) and renin mRNA in corpora lutea following gonadotrophin stimulation (Lightman et al 1987). In other species the results are also inconsistent with angiotensin receptors reported to be both present (Hayashi et al 2000, Schams et al 2003 and absent (Schauser et al 2001) in corpora lutea from cows and in low levels in pigs (Nielsen et al 1995). The reason for the discrepancies between the studies is unclear but may relate to species variations and/or modulation of the RAS by gonadotrophins at various stages of the oestrus cycle (Loret de Mola et al 1999).…”
Section: Figurementioning
confidence: 72%
“…In fact, the AngII receptor type 2 has been demonstrated to be the mediator of several reproductive functions including steroidogenesis, oocyte maturation, and ovulation (Kuji et al 1996, Ferreira et al 2007. In cows, the AngII receptor type 2 is present in the dominant follicle (Schauser et al 2001), and its mRNA expression was positively correlated with estradiol production (Portela et al 2006). In perfused rabbit ovaries, the ovulation and the meiosis resumption induced by hCG are blocked by saralasin (1-sarcosine-8-alanine-5-isoleucine-AngII, a competitive AngII antagonist; Yoshimura et al 1992).…”
Section: Introductionmentioning
confidence: 99%